Assessing the abrasivity characteristics of the central Dublin fluvio-glacial gravels – A laboratory study. (February 2020) - O'Connor, Emer; Friedman, Miles; Dahl, Filip; Jakobsen, Pål Drevland; van Oosterhout, Dirk; Long, Michael
Highlights: Large suite of laboratory abrasivity tests on fluvio-glacial gravels. Combination of well-known and newly developed tests. Very few such data reported in literature. In-situ testing also carried out. Relevance to a proposed large tunnel project in Dublin, Ireland. Abstract: The aim of this paper is to study the abrasiveness of fluvio-glacial gravels located in Central Dublin. It also seeks to identify which test types are the most suitable for assessing the impact of boring tunnels through these materials on tunnel boring machine (TBM) cutterheads. Drilling/sampling of the material proved difficult but geophysical surface wave surveying proved useful. The material was shown to be very dense and to have a large proportion of cobbles and boulders. An extensive suite of laboratory abrasiveness testing was carried out which included tests on gravel samples (e.g. SAT™, SGAT and LCPC) as well as tests on individual cobbles (e.g. point load, Cerchar, Sievers' J and SJIP). The laboratory results imply a very high impact abrasion (LCPC testing) and low to medium sliding and crushing abrasion. (SAT™ or SGAT tests). Cerchar tests on individual cobbles suggest medium abrasive material in contrast to Sievers' J/SJIP testing which indicate low surface hardness. No clear inter-relationship was found between the various test results. Similarly, no strong correlation was proven between results and various geotechnical parameters or with quartz content. The size of individual particles of gravel, cobbles and boulders could be decisive for assessment of wear. However, the larger clasts mostly comprise limestone, which are less abrasive and have a lower surface hardness. The ease of dislocating clasts from the general matrix will have an important effect on the wear on cutterhead steel. Grain angularity and sphericity of the material are important parameters for dislocation of clasts. A limitation of this and similar studies is the lack of tests capable of including particles between 10 mm and cobble size. However, it is clear that no single test can be used to assess the abrasiveness of material like the fluvio-glacial gravels encountered here.